Stereotactic Radiosurgery for Vestibular Schwannoma in Neurofibromatosis Type 2: An International Multicenter Case Series of Response and Malignant Transformation Risk. Issue 5 (2nd May 2023) - Bin-Alamer, Othman; Faramand, Andrew; Alarifi, Norah A.; Wei, Zhishuo; Mallela, Arka N.; Lu, Victor M.; Nabeel, Ahmed M.; Reda, Wael A.; Tawadros, Sameh R.; Abdelkarim, Khaled; El-Shehaby, Amr M.N.; Emad, Reem M.; et al.
Abstract : BACKGROUND: Vestibular schwannomas (VSs) related to neurofibromatosis type 2 (NF2) are challenging tumors. The increasing use of stereotactic radiosurgery (SRS) necessitates further investigations of its role and safety. OBJECTIVE: To evaluate tumor control, freedom from additional treatment (FFAT), serviceable hearing preservation, and radiation-related risks of patients with NF2 after SRS for VS. METHODS: We performed a retrospective study of 267 patients with NF2 (328 VSs) who underwent single-session SRS at 12 centers participating in the International Radiosurgery Research Foundation. The median patient age was 31 years (IQR, 21-45 years), and 52% were male. RESULTS: A total of 328 tumors underwent SRS during a median follow-up time of 59 months (IQR, 23-112 months). At 10 and 15 years, the tumor control rates were 77% (95% CI: 69%-84%) and 52% (95% CI: 40%-64%), respectively, and the FFAT rate were 85% (95% CI: 79%-90%) and 75% (95% CI: 65%-86%), respectively. At 5 and 10 years, the serviceable hearing preservation rates were 64% (95% CI: 55%-75%) and 35% (95% CI: 25%-54%), respectively. In the multivariate analysis, age (hazards ratio: 1.03 [95% CI: 1.01-1.05]; P = .02) and bilateral VSs (hazards ratio: 4.56 [95% CI: 1.05-19.78]; P = .04) were predictors for serviceable hearing loss. Neither radiation-induced tumors nor malignant transformation were encountered in this cohort. CONCLUSION: Although the absolute volumetric tumor progression rate was 48% at 15 years, the rate of FFAT related to VS was 75% at 15 years after SRS. None of the patients with NF2-related VS developed a new radiation-related neoplasm or malignant transformation after SRS. Abstract :